Correlation between CBR value and undrained shear strength from vane shear test - 212489 Noor Asmah Hussin; Khairul Anuar Kassim; Fakulti Kejuruteraan Awam (2008)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2008